EMQs for the MRCOG a guide to the extended matching questions for the MRCOG Part 2 examination - Duthie, John (Cambridge University Press, 2006)
Extended matching questions (EMQs) were introduced to the Part 2 MRCOG examination paper in September 2006. This book provides a detailed guide for candidates preparing for the examination, and includes: • background and introduction to the question format • advice on answering EMQs • worked examples of specimen questions, including an explanation of the answer, guidance on how to tackle each question and advice on how to avoid mistakes • two mock examination papers, with answers provided.